Health information systems concepts, methodologies, tools, and applications - Rodrigues, Joel 1972- (Medical Information Science Reference, 2010)
"This reference set provides a complete understanding of the development of applications and concepts in clinical, patient, and hospital information systems" - Provided by publisher
Includes bibliographical references and index
Keywords: Gesundheitsinformationssystem; Aufsatzsammlung